A FINANCIAL ANALYSIS AND SENSITIVITY ANALYSIS ON SHOPPING MALL IN KASETSART UNIVERSITY SI RACHA CAMPUS - มะลิวงษ์, ดอกอ้อ; ทวีวัฒน์, พิษณุวัฒน์ (RMUTT Global Business and Economics Review, 2015)
A Financial Analysis and Sensitivity Analysis on Shopping Mall in Kasetsart University Si Racha Campus have been conducted. The purpose of this research was the financial and sensitivity analysis of the project. These will make it possible to estimate whether the project can withstand changes in compensation and the cost of future operating. From the original project created, the study found that the possibility of financial by the age of 11 years including construction period of one year and a cost of capital of 8.42 showed that the Net Present Value (NPV) is 13,485,146 Baht. Internal Rate of Return (IRR) is 18.39 per year, meanwhile the Modify Internal Rate of Return (MIRR) is 13.34 per year. All in all, Profitability Index (PI) is 1.63 times. This study concluded that the project is financially feasible and the results of the sensitivity analysis of returns and operating costs, changes NPV, IRR, MIRR and PI. In cases, return and operating costs fell 5 percent, 10 percent, 15 percent, and 20 percent and cases of returned and operating costs increased 5 percent, 10 percent, 15 percent and 20 percent by the other variables constant in the capital cost an average weighted rate of 8.42 showed that the change in return. NPV, IRR, MIRR and PI increased by 5-20 percent and 5-15 percent reduction in costs, and changes in operating NPV, IRR, MIRR and PI 5-20 percent increase and decrease 5-20 percent. The project is worthwhile and can be changed the return on NPV, IRR, MIRR and PI decreased 20 percent to make the project could not be changed. These results show the returned of projects sensitive over cost of operations.